Developing a Javanese Language Module Through The Savi (Somatic, Auditory, Visual, Intellectual) Approach to Improve Learning Outcomes And Speaking Skills of Fourth-Grade Students at MI Perwanida, Blitar City - Febrian Dwi Kartika Sari (Universitas Islam Balitar, 2026)
This study aims to develop a Javanese language learning module based on the SAVI (Somatic, Auditory, Visual, Intellectual) approach to improve learning outcomes and speaking skills of fourth grade students at MI Perwanida Blitar city. The research employs a Research Development (R&D) design adapted from Borg and Gall's ten step model including research, product design,testing, validation, and dissemination. Data were collected through observation, interviews, questionaires, and pre-tet-post test assesments, analyzed both quantitative and qualitative methods. The result show that the develop modul meets the criteria of validity, practicality, and effectivness. Validation from material and media experts rated the module as